1999
DOI: 10.5860/crl.60.5.440
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Preferences for Search System Interfaces and the Role of Emotive Forces: A Research Challenge

Abstract: Information professionals have observed that Web-based search interfaces simplify database searching and are preferred over other interfaces. A further anecdotal observation is that their features, in comparison to other interfaces, enhance the quality of search sessions, resulting in better outcomes. One explanation is that Web interfaces ease the negative emotive forces searchers experience with other interfaces. This paper examines the challenges in designing a research method to test the validity of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Other types of user studies have attempted to study digital libraries from search and interface aspects to establish whether searchers have more success in searching with Web interfaces. An exploratory study by Bell (1999) attempted to understand whether the Web interface itself provided special``emotive'' support for researchers not provided by other types of interfaces that led to better quality in search results. Although he found that the stress level of searchers using a Web interface was lower, search results were not improved through the reduction of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of user studies have attempted to study digital libraries from search and interface aspects to establish whether searchers have more success in searching with Web interfaces. An exploratory study by Bell (1999) attempted to understand whether the Web interface itself provided special``emotive'' support for researchers not provided by other types of interfaces that led to better quality in search results. Although he found that the stress level of searchers using a Web interface was lower, search results were not improved through the reduction of stress.…”
Section: Introductionmentioning
confidence: 99%